Tris(3-nitropentane-2,4-dionato-κ2 O,O′) Complexes as a New Type of Highly Energetic Materials: Theoretical and Experimental Considerations - Danijela S. Kretić; Ivana S. Veljković; Dušan Ž. Veljković (Chemistry, 2023)
Decreasing the sensitivity towards detonation of high-energy materials (HEMs) is the ultimate goal of numerous theoretical and experimental studies. It is known that positive electrostatic potential above the central areas of the molecular surface is related to high sensitivity towards the detonation of high-energy molecules. Coordination compounds offer additional structural features that can be used for the adjustment of the electrostatic potential values and sensitivity towards detonation of this class of HEM compounds. By a careful combination of the transition metal atoms and ligands, it is possible to achieve a fine-tuning of the values of the electrostatic potential on the surface of the chelate complexes. Here we combined Density Functional Theory calculations with experimental data to evaluate the high-energy properties of tris(3-nitropentane-2,4-dionato-κ2 O,O′) (nitro-tris(acetylacetonato)) complexes of Cr(III), Mn(III), Fe(III), and Co(III). Analysis of the Bond Dissociation Energies (BDE) of the C-NO2 bonds and Molecular Electrostatic Potentials (MEP) showed that these compounds may act as HEM molecules. Analysis of IR spectra and initiation of the Co(AcAc-NO2)3 complex in the open flame confirmed that these compounds act as high-energy molecules. The measured heat of combustion for the Co(AcAc-NO2)3 complex was 14,133 J/g, which confirms the high-energy properties of this compound. The results also indicated that the addition of chelate rings may be used as a new tool for controlling the sensitivity towards the detonation of high-energy coordination compounds.